Asymmetric courtship boosts male mating success in the red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae). (March 2019) - Boukouvala, Maria C.; Romano, Donato; Kavallieratos, Nickolas G.; Athanassiou, Christos G.; Stefanini, Cesare; Canale, Angelo; Benelli, Giovanni
Abstract: Recently, the functional asymmetries of courtship and mating behavior in several major pests of economic importance at the post-harvest stages of agricultural commodities have been reported. In this study, we investigated the presence of population-level behavioral asymmetries in the red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) mating pairs. Males showed left-biased population-level courtship attempts when approaching potential mates. Furthermore, no significant differences were recorded for the duration of mate recognition and copula of males approaching females from the left, right side or backside. However, precopula and whole mating duration differ significantly among males approaching females from the left, right or backside. On the other hand, lateralization of courtship attempts had a significant impact on male mating success. Left-biased courtship attempts of T. castaneum males led to a higher male mating success, as compared to right-biased and backside courtship attempts. To the best of our knowledge, this is the first study investigating the impact of side-biased courtship attempts on male mating success in T. castaneum. Moreover, our findings add basic knowledge to the mating and reproductive behavior of this important pest that damages foodstuffs worldwide, which can be useful to optimize rearing procedures of this beetle, minimizing mating success reductions due to prolonged mass-rearing. Furthermore, knowledge about the mating behavior of T. castaneum can be utilized further towards the development of traps and attractants for this pest. Graphical abstract: Image 1 Highlights: Courtship and mating behavior of the red flour beetle, Tribolium castaneum, was analyzed. Furthermore, population-level behavioral asymmetries were evaluated. T. castaneum ♂ showed left-biased population-level courtship attempts (CA) when approaching ♀. Precopula duration differed significantly among ♂ CA from the left, right or backside. Left-biased CA of T. castaneum ♂ led to higher mating success over right-biased and backside CA.